Simultaneous UV-Spectrophotometric Estimation of Glipizide and Metformin in Bulk and Its Dosage Form - Sarangi, Rashmi Ranjan (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACT: A simple, accurate, validated and reproducible UV-Spectrophotometric method has been developed for the simultaneous estimation of Glipizide Hydrochloride and Metformin in both bulk and tablet formulation. Glipizide and Metformin in combined tablet formulation were estimated by using the multi component mode at 276 nm for Glipizide and 237 nm for Metformin in their solution in methanol. The Beerâ€™s law obeyed the concentration range of 2-20Âµg/ml for both Glipizide and Metformin. Mean recovery of 99.90% for Glipizide and 99.99% for Metformin respectively signifies the accuracy of the method. This method can be used for the routine simultaneous estimation of Glipizide and Metformin in industries and other analytical laboratories.